PENGARUH FAKTOR KEPERILAKUAN TERHADAP PENGGUNAAN SISTEM AKUNTANSI KEUANGAN DAERAH (Studi pada Badan Keuangan dan Aset Daerah Kabupaten Malang) - Gadis Ananda; Dwiyani Sudaryanti; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
This study aims to determine the effect of behavioral factors on the use of regional financial accounting systems in Malang Regency. The variables used in this study are Attitudes, Emotions, and Motivations towards the Regional Financial Accounting system. The sample in this study were 50 employees of the Malang Regency BKAD. From the results of the test using multiple linear regression, the results obtained simultaneously that the Attitude, Emotion, and Motivation variables have an effect on the Regional Financial Accounting System. Partial Testing Results show that Emotions have no effect on the Regional Financial Accounting System.Keywords: Regional Financial Accounting System, Attitude, Emotion, Motivation